A study of the effect of Mueller matrices and Stokes vectors on calculating the polarization parameters of the linear, circular, and elliptical light field. - عبدالله عماد; غياث ياسين; محمود أحمد (Latakia University Journal -Basic Sciences Series, 2024)
In this research, the polarization equation was extracted, the Stokes vectors were defined, and we performed the appropriate transformations of the optical field components in a form consistent with the Mueller matrices for polarization. We determined how to calculate the components of the matrix, which in turn determine the state and type of polarization. We demonstrated the importance of this study in calculating and knowing the optical properties such as photo activity and refractive index. The theoretical results were compared with the available and recent experimental results